2019
DOI: 10.1037/xge0000496
|View full text |Cite
|
Sign up to set email alerts
|

Negative evidence and inductive reasoning in generalization of associative learning.

Abstract: When generalizing properties from known to novel instances, both positive evidence (instances known to possess a property) and negative evidence (instances known not to possess a property) must be integrated. The current study compared generalization based on positive evidence alone against a mixture of positive evidence and perceptually dissimilar negative evidence in an interdimensional discrimination procedure. In two experiments, we compared generalization following training with a single positive stimulus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…In the present work, we focus on heterogeneity in specifications within the BLC category in comparison to one prototypical TTP approach. All of the 18 studies, except one using ANSLAB (Rattel et al, 2019) used a custom-made script whereof three studies (Ahmed & Lovibond, 2019;Lee et al, 2018Lee et al, , 2019 explicitly reported computing SCL rather than SCR. Yet, we excluded one study that investigated SCL without a baseline correction (McGlade et al, 2019), and one study that did not report any detail on SCL quantification (Kurayama et al, 2019).…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…In the present work, we focus on heterogeneity in specifications within the BLC category in comparison to one prototypical TTP approach. All of the 18 studies, except one using ANSLAB (Rattel et al, 2019) used a custom-made script whereof three studies (Ahmed & Lovibond, 2019;Lee et al, 2018Lee et al, , 2019 explicitly reported computing SCL rather than SCR. Yet, we excluded one study that investigated SCL without a baseline correction (McGlade et al, 2019), and one study that did not report any detail on SCL quantification (Kurayama et al, 2019).…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…Despite sharing many important commonalities in the way they conceptualize learning and generalization, associative learning and inductive reasoning were studied as separate literatures. Recently, researchers have started to acknowledge the importance of incorporating inductive principles in the study of fear/aversive conditioning (Dunsmoor & Murphy, 2015;Dymond et al, 2015;Hayes & Heit, 2018;Lee, Hayes, & Lovibond, 2018;Lee, Lovibond, Hayes, & Navarro, 2019;Lei et al, 2019;Lei et al, 2019). It was proposed that aversive or traumatic experiences promote inductive generalization.…”
Section: Semantic Processing Of Subliminal Wordsmentioning
confidence: 99%
“…inductive generalization differs among different types of stimuli, such as fear versus nonfear generalization in clinical populations. This could help identify the mechanisms underlying overgeneralization observed in PTSD and other anxiety disorders (Lee et al, 2019).…”
Section: Semantic Processing Of Subliminal Wordsmentioning
confidence: 99%
“…The learner updates beliefs in these hypotheses as new evidence is observed, with certain hypotheses becoming stronger and others becoming weaker. As well as changes in generalization due to additional types, Bayesian models can account for a range of inductive phenomena such as the effects of premise diversity (Hayes, Navarro, Stephens, Ransom, & Dilevski, 2019), the impact of samples containing both positive and negative evidence (Lee, Lovibond, Hayes, & Navarro, 2019;Voorspoels, Navarro, Perfors, Ransom, & Storms, 2015), and generalization based on causal rather than categorical relations (Kemp & Tenenbaum, 2009).…”
Section: The Effect Of Adding Types In Property Inductionmentioning
confidence: 99%